The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1073/pnas.0308292101
|View full text |Cite
|
Sign up to set email alerts
|

Activation of dopamine D 4 receptors by ABT-724 induces penile erection in rats

Abstract: Apomorphine, a nonselective dopamine receptor agonist, facilitates penile erection and is effective in patients suffering from erectile dysfunction. The specific dopamine receptor subtype(s) responsible for its erectogenic effect is not known. Here we report that the dopamine D4 receptor plays a role in the regulation of penile function. ABT-724 is a selective dopamine D 4 receptor agonist that activates human dopamine D 4 receptors with an EC50 of 12.4 nM and 61% efficacy, with no effect on dopamine D 1, D2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 40 publications
5
109
2
Order By: Relevance
“…McCall et al (2005) reported a 200% increase in striatal acetylcholine release in rats at doses of sumanirole roughly equivalent to those which induced yawning. The two D4-preferring agonists, given at behaviorally active doses (Brioni et al 2004;Enguehard-Gueiffier et al 2006), did not produce either yawning or hypothermia suggesting that at these doses, they are devoid of significant D2 and D3 receptor agonist activity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…McCall et al (2005) reported a 200% increase in striatal acetylcholine release in rats at doses of sumanirole roughly equivalent to those which induced yawning. The two D4-preferring agonists, given at behaviorally active doses (Brioni et al 2004;Enguehard-Gueiffier et al 2006), did not produce either yawning or hypothermia suggesting that at these doses, they are devoid of significant D2 and D3 receptor agonist activity.…”
Section: Discussionmentioning
confidence: 94%
“…As shown in Figure 1, sumanirole induced significant increases in yawning, although these increases were relatively small and observed only at the highest dose, whereas significant decreases in core body temperature were observed at lower doses; sumanirole will subsequently be referred to as a D2-preferring agonist. The D4-preferring agonists, 077 (Figure 2), failed to induce significant levels of yawning or hypothermia over a wide range of behaviorally active doses (Brioni et al 2004;Enguehard-Gueiffier et al 2006) suggesting that, at these doses, they are devoid of agonist activity at the D3 and D2 receptors. D3 values, as well as the in vivo selectivity ratios for each of the agonists.…”
Section: Agonist-induced Yawning Behavior and Hypothermiamentioning
confidence: 99%
“…782 Interestingly, normal aging in all mammalian species is associated with reduced levels of dopamine and increasing sexual dysfunction, whereas dopamine agonists enhance sexual function in both rodents and humans. 783,784 The management of male sexual dysfunction in patients with PD involves identifying and correcting any underlying treatable causes, and introducing pharmacologic therapy aimed at improving erectile function. Previously untreated or undertreated patients with PD may find that antiparkinsonian treatment helps sexual function, possibly by alleviating bradykinesia or by restoring dopaminergic tone.…”
Section: Impulse Dyscontrol and Dopamine Dysregulation Disordersmentioning
confidence: 99%
“…Adding to the complexity, apomorphine, as a non-selective dopaminergic receptor agonist, affects several types of dopaminergic receptors among them D 1 , D 2 and D 4 (Brioni and Moreland, 2006;Brioni et al, 2004;Melis et al, 2005Melis et al, , 2006Schechter and Greer, 1987), whereas chronic treatment with apomorphine may change the balance between dopamine D 1 and D 2 receptors, favoring the D 1 type (Acerbo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of dopamine D 1 vs D 2 receptors is complex (Hull et al, 1992) and hard to define, because of conflicting findings (Paredes and Agmo, 2004). The possible involvement of dopamine D 4 receptors in the pro-erectile effects of apomorphine Brioni et al, 2004;Hsieh et al, 2004) may shed new light on the existing confusing situation.…”
Section: Medial Preoptic Nucleus (Fig 2e)mentioning
confidence: 99%